Programs for Preventing Internet Addiction during Adolescence: A Systematic Review - Bağatarhan, Tuba; Siyez, Diğdem Müge (Addicta: The Turkish Journal on Addictions, 2017)
With the Internet having become an inevitable part of life, Internet addiction, being on the agenda, is viewed as a significant problem for adolescents and is frequently a subject of research. One observes that in addition to studies on the prevalence of Internet addiction during adolescence and its relation to different variables, efforts to prevent Internet addiction in adolescence in recent years have particularly started to gain importance. The number of studies on preventing Internet addiction has been rather limited compared to other types of studies, yet studies on preventing Internet addiction have great value because they allow for intervention before Internet usage becomes a problem. The aim of this research is to systematically review studies examining the effectiveness of programs that have been implemented to prevent Internet addiction during adolescence. For this purpose, the keywords of Internet addiction, Problematic Internet use, Adolescence, Prevention, Intervention, School-based, and Psycho-education have been searched in the databases of Science Direct, Pubmed, Cochrane, Wiley Online Library, and Ulakbim both in Turkish and English. The resulting 435 articles from the literature search have been evaluated according to the PRISMA guide; the selection criteria determined for this research and the five articles that met the required criteria have been included in the research. The selected articles have been examined in terms of research method, program applied, instrument used, and effectiveness of the applied program. The studies under investigation are seen to reveal positive results for preventing Internet addiction in adolescents. To